Considerations on the management of EGF receptor-TKIs for brain metastases in EGFR-mutant lung carcinoma patients. (February 2015) - Shingyoji, Masato; Iuchi, Toshihiko
SUMMARY : Approximately 20–30% of patients with NSCLC are present with brain metastases. The standard management for brain metastases is radiotherapy. Despite the administration of radiation therapy for brain metastases, the prognosis is still poor. The poor prognosis is related to the progression of extracranial lesions. Therefore, systemic therapy is important to improve survival of patients with brain metastases. EGF receptor-tyrosine kinase inhibitor (EGFR-TKI) is a standard treatment for advanced NSCLC patients with sensitive EGFR mutations and is also effective in controlling brain metastasis in such patients. Upfront EGFR-TKI therapy might be one of the treatment choices for EGFR-mutant NSCLC patients with asymptomatic brain metastases. However, it is unclear whether upfront EGFR-TKI or radiation therapy is more preferable. New EGFR-TKIs and combination with existing EGFR-TKIs and other drugs are being investigated for treatment options. Further investigations are required to determine the future direction for management of EGFR -mutant NSCLC patients with brain metastasis.